A Smorgasbord of 17 Cobalt Complexes Active for Photocatalytic Hydrogen Evolution. Issue 39 (13th June 2018) - Hogue, Ross W.; Schott, Olivier; Hanan, Garry S.; Brooker, Sally
Abstract: Seventeen cobalt complexes—eleven dinuclear cobalt(II) complexes and three tetranuclear cobalt complexes (two mixed valent) of ditopic ligands, with varying N‐donor aromatic bridging moieties and pendant pyridine side arms, as well as three mononuclear cobalt(II) complexes of Schiff base macrocyclic ligands—have been screened for photocatalytic hydrogen evolution reaction (HER) activity. All 17 complexes are active catalysts for the HER, in both DMF and aqueous solution, in tandem with the [Ru(bpy)3 ] 2+ (bpy=2, 2′‐bipyridine) photosensitiser. All are benchmarked to the literature standard [Co III (dmgH )2 (py)Cl] (dmg=dimethylglyoxime, py=pyridine) under identical conditions. Two families of dinuclear cobalt(II) complexes of bis‐tetradentate ligands that provide a triazole bridging moiety and mononuclear cobalt(II) complexes of tetradentate Schiff base macrocycles were found to be the most active catalysts, outperforming [Co III (dmgH )2 (py)Cl] by two‐ to three‐fold. Within these two families, the use of shorter alkyl linkers between the N donors, and hence, smaller chelate ring sizes, was found to significantly enhance catalytic performance, whereas the variation of peripheral functional groups was found to have little effect. This last point will be convenient for subsequent surface immobilisation studies. Abstract : Designing improved complexes : Remarkably, photocatalytic hydrogen production is observed for all 17 cobalt complexes (mono‐, di‐, and tetra‐nuclear) screened herein. The best catalysts (shown vs. cobaloxime) are two cobalt(II) complexes composed of ligands that provide five‐membered chelate rings and high denticity.